2002
DOI: 10.1176/appi.ajp.159.12.2081
|View full text |Cite
|
Sign up to set email alerts
|

Medical Service Utilization by Veterans Seeking Help for Posttraumatic Stress Disorder

Abstract: PTSD is associated with substantial health service use. The results highlight the importance of increased collaboration between primary care and mental health specialists, given that patients with PTSD are more likely to receive treatment in nonmental health clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 27 publications
11
91
0
3
Order By: Relevance
“…Another study of 996 veterans, primarily from the Vietnam era, evaluated between 1992 and 1998, demonstrated that those who met criteria for PTSD had significantly greater utilization of non-mental health outpatient services than those without PTSD (median of 18 versus 10 visits per year). 15 Other studies have demonstrated that the increase in health services utilization in veterans with PTSD is not due to comorbid psychiatric conditions, such as anxiety and depression. 26,27 Our study adds to this prior research by using national-level data, adjusting for several additional military service characteristics, and exploring utilization in OEF/OIF veterans, a group for which data are very limited.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another study of 996 veterans, primarily from the Vietnam era, evaluated between 1992 and 1998, demonstrated that those who met criteria for PTSD had significantly greater utilization of non-mental health outpatient services than those without PTSD (median of 18 versus 10 visits per year). 15 Other studies have demonstrated that the increase in health services utilization in veterans with PTSD is not due to comorbid psychiatric conditions, such as anxiety and depression. 26,27 Our study adds to this prior research by using national-level data, adjusting for several additional military service characteristics, and exploring utilization in OEF/OIF veterans, a group for which data are very limited.…”
Section: Discussionmentioning
confidence: 98%
“…11,[15][16][17][18][19] In a study of 2,508 female veterans receiving care at an urban VA medical center between 1996 and 2000, Dobie and colleagues found that after adjusting for demographics, smoking, service access, and medical comorbidities, those who screened positive for PTSD had a significantly greater likelihood of having a medical or surgical hospitalization (OR 1.37, 95% CI 1.04-1.79). 11 They were also significantly more likely to be in the highest quartile of utilization for emergency room, primary care, and ancillary services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment needs of individuals with PTSD and chronic pain must also be addressed, especially given that they are likely to use more healthcare services [75][76][77]. Thus, VA healthcare providers should be informed about the various effects of PTSD treatment on veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Negative binomial regression is a form of the Poisson regression model and is appropriate when data are overdispersed (that is, with variance greater than the mean). Overdispersion can produce underestimates of standard errors in Poisson models, leading to overstatement of statistical significance (14). In our case, the dependent variable was positively skewed, indicating that most census tracts had low rates of use and therefore that a normal distribution was not achieved.…”
Section: Analysesmentioning
confidence: 67%